WOMEN, NATURE, FANTASY: DUAL REPRESENTATION IN THE GIRL WHO DRANK THE MOON - Amalia, Emma Rifki; Istiadah, Istiadah (Sunan Kalijaga State Islamic University Yogyakarta, 2025)
This article examines the dual representation of the woman-nature connection represented by the author through elements of fantasy and the secondary world in The Girl Who Drank the Moon. This research uses a descriptive qualitative method and the lens of ecofeminism and fantasy theory to analyze data relevant to the woman-nature connection in the novel. The results show that the author uses three female characters to represent the connection between women and nature, namely Xan (witch), Luna (moon baby), and Madwoman (Adora). The connection between women and nature is depicted through two different sides. On the one hand, women and nature are depicted as loving, caring, and connected entities; but on the other hand, women and nature are depicted as dangerous entities. The use of fantasy elements such as supernatural creatures, magic, and the creation of a secondary world in The Girl Who Drank the Moon plays an important role in providing a new perspective as well as an alternative escape for readers to transcend the boundaries of various injustices against women and nature that have been normalized in the real world.